Postnatal ethanol exposure impairs social behavior and operant extinction in the adult female mouse offspring - Bariselli, Sebastiano; Reuveni, Noa; Westcott, Nina; Mateo, Yolanda; Lovinger, David M. (Frontiers in Neuroscience, 2023)
Fetal Alcohol Spectrum Disorder (FASD) comprises a group of neurodevelopmental deficits caused by alcohol exposure during pregnancy. Clinical studies suggest that while the male progeny experiences serious neurodevelopmental defects, female patients have more severe cognitive, social, and affective symptoms. Other than sex, dose, frequency, and timing of exposure determine the neurobehavioral outcomes in young and adult progeny. In this regard, human studies indicate that some individuals relapse during late-term gestational periods. In mice, this interval corresponds to the first ten days after birth (postnatal, P0-P10). In our model of postnatal ethanol exposure (PEEP0-P10), we tested whether adult female and male offspring show deficits in sociability, anxiety-like, reward consumption, and action-outcome associations. We report that female PEEP0-P10 offspring have mild social impairments and altered extinction of operant responding in the absence of anxiety-like traits and reward consumption defects. None of these deficits were detected in the male PEEP0-P10 offspring. Our data provide novel information on sex-specific neurobehavioral outcomes of postnatal ethanol exposure in female adult offspring.